Population’s knowledge about cerebrovascular accident (stroke) - passers of the square giraldo in Evora - Bule, Maria José (2016)
Stroke is the leading cause of death in Portugal and the Alentejo region. Objective: Describe the population's knowledge about risk factors, signs and symptoms of stroke. Methodology: Quantitative and cross-sectional study. Convenience sample of 207 pedestrians with ages between 16 and 86 years old (M=38,85; SD = 18.93). Results: The pathology is known, the most frequently mentioned sources of information are television and friends. Hypercholesterolemia, heart disease and smoking are the risk factors more set out. The most well known signs are numbness and weakness in the hemisphere and dysarthria. Conclusion: It is necessary to strengthen the role of health services in education about stroke. Knowledge displays weaknesses in appreciation of advanced age and diabetes. Noteworthy is the recognition of the risk associated with tobacco consumption and persistence on it.